The Aspirations, Challenges, and Influence of the Program Evaluation Standards 3rd Edition - Pauline Egelson (The Evaluation Center at Western Michigan University, 2023)
Background: The revisions to The Program Evaluation Standards, third edition (2011) were substantial. The authors of this revision were the most knowledgeable individuals to question about aspects of the PES. Purpose: To better understand the historical roots and intent of The Program Evaluation Standards, to analyze impact, and to look toward the future, it was critical to examine the aspirations, challenges, and impact associated with the PES via interviews with the authors. Setting: Not applicable. Intervention: Not applicable. Research Design:  This qualitative study included three basic interview questions, with supporting follow-up questions for each of the basic questions. Data Collection and Analysis: The results of this study were determined by the authors' responses to interview questions, which were then coded by emergent patterns and themes. Findings: Results of the interviews found that the authors aspired to provide relevant, up-to-date, and useful standards to guide evaluators, stakeholders, and students. They were able to successfully resolve challenges associated with the PES third edition revisions, and overall these resolved challenges made the edition stronger. Finally, the authors integrated the standards into their professional work, which positively influenced them, students, and other stakeholders. Keywords: program evaluation standards; interviews; aspirations; impact; challenges.